A new species of the Phanoperla pallipennis group (Plecoptera: Perlidae) from Vietnam - Mo, Raorao; Yan, Yanhua; Wang, Guoquan; Li, Weihai (Zootaxa, 2019)
A new species of the perline genus Phanoperla Banks, P. zwicki sp. nov. is described from Vietnam. The new species is compared with related taxa.